The Effect of Credit Risk, Capital Adequacy Ratio, Liquidity, Operational Efficiency, and Solvency on The Financial Performance of BPR In The City of Denpasar - Putu Kepramareni; Kadek Apriada; I Nyoman Fajar Ananta Putra; I Gusti Ayu Intan Saputra Rini (Universitas Warmadewa, 2022)
This study aims to examine the effect of the variables of Credit Risk, Capital Adequacy,Liquidity, Operational Efficiency, and Solvency on Financial Performance. Financial performance is a description of the financial condition of a company so that it can be known the good and bad financial condition of a company that reflects work performance in a certain period. This research is based on the phenomenon of increasing and decreasing profits of Bank Perkreditan Rakyat on Denpasar city in 2018-2020. The study was conducted on Bank Perkreditan Rakyat on Denpasar city conducted in 2018-2020 with a total sample of 23 and observation of 69. The method of determining the sample used was purposive sampling, namely the technique of sampling data sources with certain considerations. Data analysis techniques used multiple linear regression analysis. The results of the study found that Operational Efficiency have a negative effect Financial Performance of Bank Perkreditan Rakyat on Denpasar city in 2018-2020. While Credit Risk, Capital Adequacy, Liquidity, and Solvency do not affect Financial Performance of Bank Perkreditan Rakyat on Denpasar city in 2018-2020.